The degree of availability of the dimensions of digital citizenship values in the Islamic education courses for the secondary stage from the point of view of its teachers in Makkah Al-Mukarramah - Al-Bassam, Najla saleh (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the degree of availability of digital citizenship dimensions according to Saudi Vision 2030 in Islamic education courses for the secondary stage from the point of view of Islamic education teachers, The study studies the descriptive curriculum, and the study population comprises all the Islamic education teachers for the secondary stage, As for the sample, it consisted of 48 teachers, and the tool was a questionnaire that was confirmed and validated, and among the most important results that the study reached: That the degree of Digital citizenship in Islamic education courses for the secondary stage Medium degree, She indicated that there are no statistically significant differences at the level of significance (α≤0.05)  between the average response of the respondents according to the variable (years of experience - academic grade), and among the most important recommendations of the study: work to include Islamic education courses on the dimensions of digital citizenship, and the most important proposals for the study: Evaluation of the Islamic Education headquarters for other levels in light of digital citizenship.
Keywords: Islamic education; digital citizenship; secondary school; Makkah Al-Mukarramah